Pengembangan Aplikasi E-Money Dengan Pemanfaatan Payment Gateway Berbasis Android (Studi Kasus Sekolah Tinggi Teknologi Indonesia Tanjungpinang) - Dwi Nurul Huda; Tio Adyatma; Zulfachmi Zulfachmi (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2022)
In previous research, a website-based e-money application has been developed which will be implemented at the STT Indonesia Tanjungpinang annual event, namely the student market but still has several shortcomings including the process of exchanging real money into digital money which is still done manually by the admin which causes the application it becomes less effective Therefore, the application was developed into an Android-based e-money application and added several additional features such as being able to use the payment gateway feature and the generate QR Qode feature that can be accessed through a gadget scanner. This application is designed using the Waterfall (Classic Life Cycle) software development method and also uses some software that supports the design of the e-money application such as programming language using Hypertext Preprocessor (PHP) and database management using phpMyAdmin as database, then for Text editor. using the Visual Studio Code application, and the web server using the XAMPP application. This research produces a more dynamic and userfriendly program that can be accessed on the gadgets of each visitor or seller and this program can also perform buyer data processing, seller data processing, menu selection and sales reports and product purchases at the STT Indonesia Tanjungpinang student market this program can monitor all transactions that occur between buyers and sellers so as to minimize errors that can occur in the STT Indonesia Tanjungpinang student market.